Management of Scout Extracurricular Activities in Improving Non-Academic Achievements of Students at Islamic Senior High Schools - Fatchudin, Fatchudin; Arifah, Umi; Adib, Shohibul; Salim, Agus; Fatimah, Siti (Lembaga Bale Literasi, 2025)
This research aims to determine the management of scout extracurricular activities in improving the non-academic achievements of students at Madrasah Aliyah Raudlatul Huda Adipala. This research method uses a qualitative approach, and data collection techniques include observation, interviews, and documentation. The collected data from these techniques were analyzed using the Miles and Huberman and Saldana model, employing four stages: data collection, data condensation, data presentation, and data verification. The research results indicate that the management of Scout Extracurricular Activities in Improving Non-Academic Achievements of Students at Madrasah Aliyah Raudlatul Huda Adipala has been well-planned, programmed, implemented, and evaluated through three stages: the planning stage, the implementation stage, and the evaluation stage, which are carried out as follows: The formulation stage of strategic extracurricular management, where a SWOT analysis is conducted. The application process of programs and activities/actions to be carried out by all units based on the principal's policies. All policies made by the principal involve all stakeholders. The evaluation of scout extracurricular management is carried out by measuring the extent to which the objectives have been achieved and how effective the management strategies implemented have been.